Micro e macroimpactos de políticas de desenvolvimento regional: O caso dos empréstimos do FNE-industrial no estado de Ceará - Guilherme Mendes Resende (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The main goal of this paper is to combine micro and macro-evaluations of the Constitutional Financing Funds for the Northeast (FNE) focusing on the analysis of Ceará state in order to control for spatial heterogeneity. It aims to measure the impact of the FNE industrial loans on employment and labour productivity growth at the micro (firm) level and on GDP per capita growth at macro (municipalities) levels for the 2000-2003 and 2000-2006 periods. The case of Ceará may help to better understand the results obtained for the Northeast region as a whole. In fact, the results suggest that micro and macro-impacts of FNE-industrial in the state of Ceará have a higher magnitude than those observed in the Northeast region as a whole.
Keywords: C52; R58; 330; impact evaluation; FNE; Ceará